PERAN MEDIA SOSIAL, MINAT BERWIRAUSAHA, DAN PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KEBERHASILAN KEWIRAUSAHAAN DIGITAL DI KABUPATEN SUMBAWA - Irnaria; Hardiansyah, Rian (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to examine the influence of Social Media Role, Entrepreneurial Interest, and Information Technology Usage on the Success of Digital Entrepreneurship in Sumbawa Regency. Employing a quantitative approach and survey method, the research collected data from digital business practitioners in Sumbawa Regency through online-distributed questionnaires. The obtained data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) to test the relationships among variables. The findings indicate that Social Media Role exerts a positive and significant influence on digital entrepreneurship success, as the utilization of social media can enhance market visibility and reach. Furthermore, Entrepreneurial Interest was proven to have a significant impact, with individuals possessing high interest tending to be more proactive in initiating and developing digital ventures. Information Technology Usage was also found to have a positive and significant effect, enabling entrepreneurs to improve efficiency and expand markets. Overall, this research affirms that these three factors substantially contribute to the success of digital entrepreneurship in Sumbawa Regency and provides recommendations for enhancing digital literacy and social media utilization among young entrepreneurs.